Assessing training needs in health research ethics: a case study from the University of Zambia School of Medicine. Issue 1 (1st January 2020) - Chongwe, Gershom; Sikateyo, Bornwell; Kampata, Linda; Ali, Joseph; Hallez, Kristina; Hyder, Adnan A.; Kass, Nancy; Michelo, Charles
ABSTRACT: In many settings, and perhaps especially in low-middle income countries, training institutions do not adequately prepare their students for the ethical challenges that confront them in professional life. We conducted a survey to assess the training needs in research ethics among the faculty at the University of Zambia, School of Medicine (UNZASoM) using a structured questionnaire distributed to faculty members in January 2015. The study was approved by the University of Zambia Biomedical Research Ethics Committee. Seventy-five faculty members of various ranks completed the questionnaire. It was found that 31% of the faculty had not received any research ethics training. Of those who had received training, most of them had received it through short workshops of five days or less (57.4%, n = 31), while only 27.7% received ethics training as a component of an academic degree and 22.2% obtained it through electronic web-based courses. While most faculty (70.7%) reported being well-prepared to guide their students in developing a research methods section of a research protocol, only 25.3% felt they were well-prepared to guide on ethical considerations. This study has demonstrated gaps in research ethics training among faculty members at UNZASoM. Mandatory instruction in research ethics among faculty and students is recommended.